PENATALAKSANAAN FISIOTERAPI DENGAN PENERAPAN KOMBINASI MYOFASCIAL RELEASE DAN NEUROMUSCULAR TAPING (NMT) DALAM MENINGKATKAN FUNGSIONAL KAKI PADA KONDISI PLANTAR FASCIITIS - Yose Rizal (LPPM Universitas Abdurrab, 2023)
Plantar fasciitis is the most common diagnosis for heel pain. Plantar fasciitis is degeneration of the plantar fascia due to repeated micro-tears in the fascia that cause an inflammatory reaction and is not a primary inflammatory process as most people believe. The cause of plantar fasciitis is unknown but is believed to be multifactorial, with abnormal biomechanics and delayed healing being the most likely causes. The purpose of this study was to determine the decrease in plantar fasciitis pain after Myofascial Release and Neuromuscular Taping (NMT) interventions. This study uses the case study method. The sample for this study was a 28-year-old man who was given physiotherapy intervention in the form of a combination of Myofascial Release and Neuromuscular Taping (NMT) 12 times for 4 weeks. The functional value of the foot is measured by the Foot Function Index (FFI). The results of the study showed that Myofascial Release and Neuromuscular Taping (NMT) could improve foot function in plantar fasciitis patients.